2022
DOI: 10.3390/ijerph192013276
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Vertebral Hemangioma and Spinal Cord Compression: A Particular Direct Access Case of Low Back Pain to Be Managed—A Case Report

Abstract: Hemangiomas are the most common benign tumours affecting the spine, with an incidence of 10–12% of the general population. Although most hemangiomas are asymptomatic, there are aggressive forms which can develop symptoms, leading patients to show signs of disability. This case report aims to highlight the importance of red flags screening, and to report the physiotherapist’s clinical reasoning that led him to refer his patient to other healthcare professionals. This case also illustrated the pre- and post-surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Surgery is a relatively effective treatment for invasive sacral hemangioma, but early diagnosis and treatment and postoperative rehabilitation are critical steps for comprehensive treatment, as they can ensure avoiding excessive damage to neurological function and facilitate the recovery of neurological function after surgery. In 2022, Brindisino et al reported a case of invasive VH with spinal cord compression, which highlighted the importance of rapid clinical diagnosis and treatment as well as postoperative rehabilitation planning with rehabilitation physicians for postoperative neurological recovery ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is a relatively effective treatment for invasive sacral hemangioma, but early diagnosis and treatment and postoperative rehabilitation are critical steps for comprehensive treatment, as they can ensure avoiding excessive damage to neurological function and facilitate the recovery of neurological function after surgery. In 2022, Brindisino et al reported a case of invasive VH with spinal cord compression, which highlighted the importance of rapid clinical diagnosis and treatment as well as postoperative rehabilitation planning with rehabilitation physicians for postoperative neurological recovery ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myofascial therapy, muscle-strengthening exercises, and mobilization treatments are gradually introduced as the rehabilitation program progresses. The patient's physical strength and mobility are being gradually rebuilt through this step-by-step process [19]. In another study, carried out by Chu and Leung, the patient underwent conservative treatment, including robotic traction therapy and thoracic spinal adjustments, to address intervertebral limitations while maintaining the hemangioma site pristine [20].…”
Section: Discussionmentioning
confidence: 99%
“…Back pain is sometimes a permeance of scoliosis, which leads to the neglect of the diagnosis of scoliosis. Early differential diagnosis to exclude other severe problems is particularly important [ 15 17 ]. Poor prognosis is more often appeared in untreated patients with severe rigid spinal deformity, with approximately 5% of them developing chronic respiratory failure as adults [ 18 ].…”
Section: Discussionmentioning
confidence: 99%